The Effect of Introducing Basic English through Multimodal Learning on Learning Activities of Kindergarten Students - Oktavia Ilmiasari; Indah Arvianti; Eko Heriyanto (English Literature Department, Faculty of Economics, Law, and Humanities, 2023)
Language acts as a means of communication between people. At an early age, language is a tool to develop intellectual abilities that develop rapidly and thoroughly. By the principles of learning in kindergarten, the introduction of English in kindergarten should also be delivered in a fun way, using interesting media. The purpose of this study is to introduce basic English in kindergarten using aspects of multimodal learning. This study uses Anstey and Bull's multimodal theory. Multimodal learning is the use of various media in the learning process. The multimodal, there are five aspects in it, namely linguistic aspects, visual aspects, audio aspects, gestural aspects, and spatial aspects, and the subjects of this study are students from Masehi Citandui Kindergarten, Semarang. This research uses case studies. The authors use the following data collection methods: interviews, documentation, and observations. The results showed that the use of multimodal learning in teaching basic English to kindergarten students gained good effect, namely students become active, creative, confident, and begin to understand basic English, as evidenced when the author teaches by giving exercises and some assignments and repetition of material in the specified learning session.